Custom-built rigs, customized conciousness among women truck drivers - Smith, Elaine Gloria (My University, 1991)
This research examines a specific form of gender consciousness among women truck drivers that emerges from the social relations of work and" the social relations of gender. Through in depth interviewing of women truck drivers in Ontario, valuable information was gathered that reveals the motivations for entering this occupation, the social relations within the family, and the structural constraints on women who work in this nontraditional occupation. The focus of this study encompasses both paid labour and unpaid household responsibilities, and the interconnections between the two, as women consciously attempt to balance this workload. In both workplaces, class and gender relations predominate in discussions related to the structural constraints placed on women. However, the most remarkable discovery is the manner in which women truck drivers borrow beliefs and ideas from two competing gender ideologies in order to justify their own lives. By meticulously selecting contradictory ideas and values from both patriarchal and feminist ideology, these women create an individual customized gender consciousness· that is constructed to suit their own material existence. This research, therefore, synthesizes both gender consciousness and the working lives of women truck drivers--two topics of which very little information has previously been documented, particularly from a Canadian perspective.
Keywords: Sociology; Sociology